Ways to Eliminate Viral Hepatitis as a Global Health Threat - Robert Flisiak; Dorota Zarębska-Michaluk; Marta Flisiak-Jackiewicz (Viruses, 2022)
Hepatitis B (HBV) and C (HCV) have been recognized by the World Health Organization [...]